Equations of motion in general relativity - Asada, H. (Hideki); Futamase, Toshifumi, 1953-; Hogan, P. A. (Peter A.) (Oxford : Oxford University Press, 2011)
Einstein's theory of general relativity describes the gravitational field of a system of stars and predicts their paths by providing the 'equations of motion' of each star. Extracting these equations from his field equations is a highly technical procedure described in this book.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Dec. 16, 2010).
Keywords: Stars -- Proper motion; Stars -- Orbits; General relativity (Physics); Astronomy -- Mathematics